High mannose level in bladder cancer enhances type 1 fimbria–mediated attachment of uropathogenic E. coli - Maalouf, Naseem; Gur, Chamutal; Yutkin, Vladimir; Scaiewicz, Viviana; Mandelboim, Ofer; Bachrach, Gilad (Frontiers in Cellular and Infection Microbiology, 2022)
Bladder cancer is the 4th leading cancer in men. Tumor resection followed by bladder instillation of Bacillus Calmette-Guérin (BCG) is the primary treatment for high-risk patients with Non-Muscle Invasive Bladder Cancer (NMIBC) to prevent recurrence and progression to muscle-invasive disease. This treatment, however, lacks efficiency and causes severe adverse effects. Mannose residues are expressed on bladder surfaces and their levels were indicated to be higher in bladder cancer. Intravesical instillations of a recombinant Pseudomonas aeruginosa (PA) overexpressing the mannose-sensitive hemagglutination fimbriae (PA-MSHA), and of a mannose-specific lectin-drug conjugate showed efficiency against NMIBC in murine models of bladder cancer. Urothelial mannosylation facilitates bladder colonization by Uropathogenic E. coli (UPEC) via the interaction with the FimH mannose lectin, positioned at the tip of type 1 fimbria. A recombinant BCG strain overexpressing FimH on its outer surface, exhibited higher attachment and internalization to bladder cancer cells and increased effectivity in treating bladder cancer in mice. Investigating the pattern of mannose expression in NMIBC is important for improving treatment. Here, using tissue microarrays containing multiple normal and cancerous bladder samples, and lectins, we confirm that human bladder cancer cells express high mannose levels. Using UPEC mutants lacking or overexpressing type 1 fimbria, we also demonstrate that tumor-induced hypermannosylation increases type 1 fimbria mediated UPEC attachment to human and mouse bladder cancer. Our results provide an explanation for the effectiveness of PA-MSHA and the FimH-overexpressing BCG and support the hypothesis that mannose-targeted therapy holds potential for improving bladder cancer treatment.